Review of Checklist and Global Rating Form Scoring Methods in Objective Structured Clinical Examination Stations: A Narrative Review - Mahla Salajegheh; Nazanin Shamaeian Razavi (Kerman University of Medical Sciences, 2021)
Background: The objective structured clinical examination (OSCE) is broadly applied to assess the clinical competence of medical students. Despite the widespread use of the OSCE, the scoring methods used in this test can be a potential source of measurement error and affect the accuracy of the scores.Objectives: This study was aimed to investigate the checklist and global rating form scoring methods in OSCE stations.Methods: In this narrative review study, the keywords "OSCE", "Reliability", "Validity", "Utility", "Global", and "Checklist" were searched in Scopus, Web of Science, EMBASE, and Medline databases between 2010 and March 2021. After removing duplicates and considering the direct relationship of the articles to the study's objectives, full-text articles were reviewed.Results: In total , 30 articles were retrived, of which 19 cases were finalized. The results of retrived articles were divided into five categories, including the correlation of scores, subjectivity and objectivity, validity and reliability, ease of use, and the need to train assessors, and the assessed capabilities in scoring by checklists and global rating forms.Conclusion: There is widespread disagreement on the superiority of checklist over global rating form. It is recommended that both scoring methods be used in combination to achieve maximum reliability and validity, to assess student skills based on objective criteria, to avoid applying assessor mentality, and to gain maximum validity in test results.